2022
DOI: 10.1002/he.20451
|View full text |Cite
|
Sign up to set email alerts
|

“It Was Rough”: The experiences of first‐generation collegians transitioning into higher education amid COVID‐19

Abstract: During the global health pandemic caused by COVID-19, most collegians and higher education agents abruptly transitioned to online learning and virtual interactions. Although online education is not a new phenomenon, this was an unforeseen transition for most students in higher education. This study investigated what first-generation collegians in their 1st year and 1st-year transfers experienced at a public university in the northeast United States during the 2020-2021 academic year. Findings include increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The change was smooth for some; however, many students with disabilities and students without adequate utilities and Wi-Fi experienced additional difficulties transitioning to remote learning (Scott & Aquino, 2020;Tachine, 2022). In a phenomenological study conducted by Santa-Ramirez et al (2022) on the transitional college experiences of first-generation, first-year, and first-year transfer students during the 2020-2021 academic year in the Northeast region of the United States-with the majority of Black, Indigenous, and People of Color (BIPOC) student collaborators-the authors found that these collegians experienced increased isolation and mental health issues and the hardships with finding and building community with faculty, staff, and peers. Further, due to the COVID-19 pandemic, the national student survey data from higher education institutions in the United States and Canada highlighted a significant decrease in students' sense of belonging to their universities and a decline in learner engagement (NSSE, 2021;Tice et al, 2021).…”
Section: Effects Of Covid-19 and Racial Unjustmentioning
confidence: 99%
See 2 more Smart Citations
“…The change was smooth for some; however, many students with disabilities and students without adequate utilities and Wi-Fi experienced additional difficulties transitioning to remote learning (Scott & Aquino, 2020;Tachine, 2022). In a phenomenological study conducted by Santa-Ramirez et al (2022) on the transitional college experiences of first-generation, first-year, and first-year transfer students during the 2020-2021 academic year in the Northeast region of the United States-with the majority of Black, Indigenous, and People of Color (BIPOC) student collaborators-the authors found that these collegians experienced increased isolation and mental health issues and the hardships with finding and building community with faculty, staff, and peers. Further, due to the COVID-19 pandemic, the national student survey data from higher education institutions in the United States and Canada highlighted a significant decrease in students' sense of belonging to their universities and a decline in learner engagement (NSSE, 2021;Tice et al, 2021).…”
Section: Effects Of Covid-19 and Racial Unjustmentioning
confidence: 99%
“…I found these practices to be highly beneficial for building trust and rapport with my students and humanizing their holistic experiences. Santa-Ramirez et al (2022) found that students felt a greater connection to their faculty members amid COVID-19 and virtual learning when they had their cameras on and made an effort to get to know their students on a personal level. I would be remiss not to mention that I understand these choices have certain privileges, and not all faculty have this capacity and availability.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salgın sürecindeki öğrenci odaklı çalışmalar, genel olarak öğrenciler arasında ortaya çıkan eşitsizlikler ve güçlükleri vurgularken, bunlar nedeniyle birinci nesil üniversite öğrencileri arasında çok daha fazla sorun yaşanmasına neden olduğunu ortaya koymuştur. Bu sorunları kısaca şu şekilde sıralamak mümkün: kapanmalara bağlı olarak izolasyon sorununun yol açtığı zihinsel sağlık sorunları, yüksek kaygı, stres ve yalnızlık duygusu, akran ve öğretim üyeleri ile iletişim kopukluğu, aidiyet duygusunda düşüşe bağlı okul terki, akademik ve sosyal etkinliklerden mahrumiyet, aile yanına geri dönüş, aile içindeki sorumluluklarda ve bakım emeğinde artış, ekonomik güvensizlik, aile üyelerinin maaş kaybı, artan yaşam ve teknoloji harcamaları gibi ekonomik zorluklar, yetersiz çalışma alanları, teknolojik kaynaklara erişim sorunu, çevrimiçi eğitime uyum, devam ve katılım zorluğu (Baum, 2020;Soria vd., 2020;Barber vd., 2021;Davis vd., 2021;Santa-Ramirez, 2022b;Kiebler ve Stewart, 2022). 6 Görüldüğü gibi var olan güçlüklerle birlikte, COVID-19'a bağlı olarak eklenen yeni güçlükler ve zorluklar birinci nesil için bu dönemin çok daha zor koşullarda deneyimlenmesine neden olmuştur.…”
Section: Sad / Jsrunclassified